Preparation and evaluation of antigens for use in a complement fixation test for Trypanosoma evansi - Quinlan, James Finbarr (The University of Edinburgh, 1976)
Stabilate of a South American strain of Trypanosoma evansi, TREU 1292, taken from storage at -79°C was thawed, mixed with Locke's solution and given to mice by intraperitoneal injection. The strain was passaged at 3 day intervals until the number of trypanosomes had increased sufficiently to be passaged into rats. When so passaged its virulence was such as to cause a teeming parasitaemia in the rats in 2 to 3 days. The blood was collected from the rats at the peak of parasitaemia and the parasites separated from the blood by a combination of two techniques, namely differential centrifugation followed by DEAE cellulose separation. The resulting suspension of trypanosomes, after division into separate portions, was treated to produce the following antigens: • Antigen 1. Glycerine and formalin treated trypanosomes (Watson 1915) • Antigen 2. Sonicated trypanosomes (Gill 1965) • Antigen 5» Freeze/Thawed trypanosomes (Lotzsch and Deindl 1974) The sera used to test these antigens were produced in rabbits. A preinfection and 37 day post infection serum from a rabbit (R202) which had been infected with TREU 1292 was used as the homologous system. A similar set of sera from a rabbit (R255) which had been infected with a West African strain of T. evansi TREU 1286 was used as the heterologous system. The complement fixation test used was a checker/board system using 80 well W.H.O. perspex plates. Dilutions of antigen, serum and complement were stored overnight at 4°0 before the addition of the haemolytic system to the plates. The plates were shaken on an automatic shaker in a walk-in incubator at 37°C for 45 minutes. They were then removed and returned to 4 0 to allow settling of unlysed H.B.Cs. to take place and read after 3-4 hours. Antigens 1 and 3, in two series of tests, Series A and Series B, proved to be the least satisfactory. They showed anticomplementary effects in the antigen control wells and nonspecific complement fixation with the preinfection sera. Antigen 2 gave the most promising results. When freshly prepared there was neither anticomplementary effect nor nonspecific complement fixation. There was, however, a suggestion that after 3 months storage some deterioration in the specificity of the antigen took place.
The preparation and evaluation of antigens for use in a complement fixation test for Trypanosoma evansi
Keywords: Annexe MSc Digitisation Project 2022 Block 37